Enhanced melanoidin removal by amine-modified Phyllanthus emblica leaf powder. (November 2021) - Verma, Rahul; Kundu, Lal Mohan; Pandey, Lalit M.
Highlights: Optimization of parameters for melanoidin removal by Response Surface Methodology. Enhanced adsorption capacity by 2.5 folds after surface modification with amine SAMs. Max. adsorption capacity of 616.2 mg g −1 by amine-modified Phyllanthus emblica leaf. 91 ± 3 % of colour removal and 84 ± 2 % of COD reduction from a real spentwash sample. Adsorption through surface attachment, complexation and electrostatic interactions. Abstract: Melanoidins are classified as hazardous colouring and polluting biopolymers, which are generated in very large amounts in molasses-based distillery effluent. In this study, melanoidin was removed through adsorption using amine surface-modified Phyllanthus emblica leaf powder (PELP) as a low-cost natural adsorbent. The amine-modified adsorbents were prepared by forming self-assembled monolayers (SAMs). The pzc of melanoidin and anime-modified PELP were found to be 6.9 and 3.8, respectively. RSM-CCD was used to optimize the environmental conditions considering adsorbent doses (0.2–2 % w/v), pH (3–11) and temperature (25–55 °C). A complete decolourization of melanoidin (98.50 ± 1 %) was observed at the optimized conditions (44.0 °C, pH = 5.93 and dose = 1.34 % w/v) along with 93.4 ± 0.2 % of COD reduction. The surface modification enhanced the maximum adsorption capacity to 616.2 mg g −1 i.e. 2.5 folds. The modified adsorbent also resulted in colour removal and COD reduction as 91 ± 3 and 84 ± 2 %, respectively from a real spentwash sample.